Review of Gelar Reservoir Operation Simulation in Jembrana Regency - Nuraga, I Ketut; Putri , Putu Indah Dianti (Fakultas Teknik, Universitas Brawijaya, 2025)
As one of the most vital natural resources, water resources must be utilized and handled carefully and comprehensively. Water utilization for irrigation and drinking water is one of the various alternative uses of water in a river basin. In the East Tukad Daya river area, Jembrana Regency, a preliminary study has been carried out regarding plans to build a reservoir or dam to meet the irrigation water needs of 1,198 hectares and drinking water for the community in Melaya District and parts of Kota Negara. This research aims to simulate reservoir operations to ensure the reliability of storage operations in meeting existing water needs. The analytical method used is a simulation method based on the water balance formulation in the reservoir. The reservoir storage simulation results showed that the total storage capacity was 1,350.514 x 103 m3 at an overflow lighthouse height of + 180.0 m. The dead storage due to sedimentation is 12.817 x 103 m3, so the height of water withdrawal at the low water level (LWL) is set at an elevation of + 158.71 m. Based on the total area of storage and dead storage, the effective storage is 1,337.697 x 103 m3. This research provides an overview of the operating patterns that can be used as a reference for discharge release operations according to the service area’s needs.